The economics of the division of labour in early Chinese literature: With particular comparison to the ancient Greek thought - Sun, Guang-Zhen (The European journal of the history of economic thought, 2016)
Like their Greek counterparts, a number of Chinese thinkers of the "Axial Period" wrote extensively on the division of labour. In particular, Kuan Chung, Hsün Tzu and Ssu-ma Ch'ien explicitly discussed economic issues related to the division of labour, contributing sophisticated analysis on the subject. In this article, we first examine Kuan Chung and his followers' fairly interesting analysis of the economies of agglomeration of specialists, and Ssu-ma Ch'ien's deep insight into the Taoist invisible hand of the market in coordinating the division of labour. The common ground between them is a sound understanding of the role of market exchange in facilitating the social division of labour, but the latter goes much further in appreciation of the spontaneous market order. We then turn to Hsün Tzu's profound scholarship of specialised learning or doing and his Confucian theory of the origin of social division, highlighting, in particular, his Confucian notion of natural equality and utilitarian account of the formation of society. Similarity in profundity and influence notwithstanding, of greater interest, appears to be the remarkable differences between the Chinese scholars and the philosophers of classical Athens in respect of their study of the division of labour, and we therefore investigate how and why the Chinese treatment contrasts thus sharply with the Greek/Europeans.